2012
DOI: 10.2105/ajph.2011.300435
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Communication Inequalities to Disparities in Human Papillomavirus Vaccine Awareness and Knowledge

Abstract: Use of a communication channel, such as the Internet, whose use is already socially and racially patterned, may widen observed disparities in vaccine completion rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 33 publications
6
58
0
Order By: Relevance
“…Awareness of the HPV vaccine was relatively high in our sample; more than three-quarters of participants (77%) had heard of the HPV vaccine before completing the questionnaire. Although some studies have documented a similar level of awareness (Sandfort & Pleasant, 2009), others have reported lower awareness (Blake et al, 2015;Kontos, Emmons, Puleo, & Viswanath, 2012;Laz et al, 2013;Osazuwa-Peters et al, 2015). Nonetheless, less than onehalf of our population (45%) recalled having a prior conversation about HPV and/or the HPV vaccine with a health care provider.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…Awareness of the HPV vaccine was relatively high in our sample; more than three-quarters of participants (77%) had heard of the HPV vaccine before completing the questionnaire. Although some studies have documented a similar level of awareness (Sandfort & Pleasant, 2009), others have reported lower awareness (Blake et al, 2015;Kontos, Emmons, Puleo, & Viswanath, 2012;Laz et al, 2013;Osazuwa-Peters et al, 2015). Nonetheless, less than onehalf of our population (45%) recalled having a prior conversation about HPV and/or the HPV vaccine with a health care provider.…”
Section: Resultsmentioning
confidence: 66%
“…Previous research has also found that people receive HPV information from the media, including television commercials (Sandfort & Pleasant, 2009), news programs (Kelly, Leader, Mittermaier, Hornik, & Cappella, 2009), and radio, magazines, or the Internet (Osazuwa-Peters et al, 2015). One study found that Internet users have greater awareness of HPV and the HPV vaccine than Internet non-users (Kontos et al, 2012). Although women may learn about HPV from other sources, many report a preference for receiving HPV information from their health care provider, suggesting that providers can be a trusted source of information (Bellinger, Millegan, & Abdalla, 2015;Joseph et al, 2014;Sandfort & Pleasant, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Results from the Health Information and National Trends Survey (HINTS) in the United States and an Australian survey show the public to be increasingly engaged with online health information (18)(19)(20)(21). In the cancer field, use of online information by cancer survivors is well documented (22)(23)(24)(25)(26), and the Internet is being used as a resource for cancer-related information in the general population (27). These findings are complemented by evidence that online behavior change materials can achieve comparable effects to print-based or telephone modalities (28,29).…”
Section: Introductionmentioning
confidence: 99%
“…Because the subjects we recruited had access to the Internet and volunteered to participate in the survey, there may have been a certain degree of selection bias. Considering social stratification, the percentage of people who had a history of viral hepatitis testing in this study might have been higher than that in the general working generation population 22) .…”
Section: Discussionmentioning
confidence: 61%